The effect of content knowledge workshop on the written test performance of physical education students - Gao, Yongqi; Soh, Kim Geok; Zakaria, Noor Syamilah; Mohd Rasdi, Roziah; Soh, Kim Lam (AIP Society India, 2022)
In this paper, the workshop teaching method and standardized teaching method (two teaching methods) are used to intervene in a teaching experiment conducted among the students of the same level. The teaching experiment is divided into the workshop method and standard teaching groups with the aim of analysing the influence of these teaching methods on students' achievement. Two kinds of teaching methods were used to intervene in the six-week teaching experiment, and the students were given three written tests in the form of test papers. The total score of the test paper was 100. The test paper includes six groups of knowledge modules: sports training design (STD), competition venue planning (CVP), movement energy metabolism (MEM), and the teaching design (TD) as well as knowledge of movement techniques (KMT) and movement rules (KMR). The main purpose of the written tests were to determine whether the workshop teaching method improved the students' written test performance compared to the standard teaching method. Data was used to test the effectiveness of the research. The experiment found that the scores of students in the workshop teaching group to be significantly higher than those in the standardized teaching group.